KEBIJAKAN INDONESIA TERHADAP PERKEMBANGAN OLAHRAGA ELEKTRONIK (E-SPORTS) DI DUNIA - Eko Rizki Saputro; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Playing online games has now developed into a professional competition that is internationally recognized. Indonesia as an actor in the international world also cannot avoid the impact of the development of e-Sports. The development of e-Sports in Indonesia can open up good opportunities, but can also be a threat if it is not handled properly by the Indonesian government. Therefore, this study was made to find out what policies will be taken by the Indonesian government to deal with the development of e-Sports in the world.This study uses a descriptive qualitative method, along with a Globalist perspective and the Concept of Foreign Policy by K.J Holsti. The use of a Globalist perspective is considered very relevant to the issues discussed by researchers, because basically the development of e-Sports is an issue of globalization. Then the concept of Foreign Policy is used to examine the policies taken by the Indonesian government in dealing with the development of e-Sports.Based on the data that the authors collect, Indonesia has made a series of policies to deal with the development of e-Sports in the world. First, Indonesia formed an official body that regulates e-Sports in Indonesia, namely the Indonesia e-Sports Association (IeSPA). Second, Indonesia issued a Regulation of the Minister of Communication and Information on the Classification of Electronic Interactive Games. The three Indonesians are also developing digital infrastructure to support the development of e-Sports in Indonesia through the Palapa Ring and Base Transceiver Station projects. Finally, Indonesia is also developing an e-Sports ecosystem in Indonesia by providing support to Indonesian game developers, as well as organizing national and international tournaments.Although the policies taken by the government are quite lagging behind other countries, the Indonesian government remains committed and makes efforts to support the development of e-Sports in Indonesia.Key Words: Game Online, e-Sports, Indonesian Foreign Policy.